2016
DOI: 10.1016/j.jbiosc.2015.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characterization of a novel thermophilic α-galactosidase from Talaromyces leycettanus JCM12802 with significant transglycosylation activity

Abstract: Thermophilic α-galactosidases have great potentials in biotechnological and medicinal applications due to their high-temperature activity and specific stability. In this study, a novel α-galactosidase gene of glycoside hydrolase family 27 (aga27A) was cloned from Talaromyces leycettanus JCM12802 and successfully expressed in Pichia pastoris GS115. Purified recombinant Aga27A (rAga27A) was thermophilic and thermotolerant, exhibiting the maximum activity at 70°C and retaining stability at 65°C. Like most fungal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…The thermophilic Talaromyces spp. are known to be potential industrial enzyme producers, as they have been reported to secrete various kinds of hydrolytic enzymes such as mannanase [ 19 ] and α-galactosidase [ 20 ]. However, no β-glucanase of GH16 has been reported from this genus yet.…”
Section: Introductionmentioning
confidence: 99%
“…The thermophilic Talaromyces spp. are known to be potential industrial enzyme producers, as they have been reported to secrete various kinds of hydrolytic enzymes such as mannanase [ 19 ] and α-galactosidase [ 20 ]. However, no β-glucanase of GH16 has been reported from this genus yet.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, ReGal2 exhibited a significant tolerance to SDS and β-mercaptoethanol with hardly any activity lost when treated with SDS or β-mercaptoethanol up to 200 mM, which is in agreement with the observation that it retained the active oligomeric state during electrophoresis in the presence of these two denaturants. This is quite unique among the so far characterized α-galactosidases, which markedly lost activities in the presence of SDS (Table 5) [9, 10, 12, 3133]. Even more surprisingly, ReGal2 did not show reduced activity in the presence of urea (up to 200 mM), and maintained approximately up to 80% of its initial activity in the presence of GdnHCl (200 mM), which is a stronger denaturant than urea.…”
Section: Resultsmentioning
confidence: 75%
“…High structural stability is also an important and desirable feature of enzymes to resist toxic inhibitors either derived from the substrate or generated during the reaction. Compared to extensive studies on the mesophilic α-galactosidases, only a few thermophilic/thermostolerant α-galactosidases have been characterized, most of which are from thermophilic fungi (see a summary in Table 1), e.g ., Neosarotrya fischeri [9, 10], Thermomyces lanuginosus [11], Talaromyces leycettanus [12], and Talaromyces emersonii [13]. These α-galactosidases exhibit various degrees of thermo-activity and thermo-stability as well as resistance to a number of metal ions and some other chemicals (see a summary in Table 5).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, when melibiose was used as the substrate, the enzyme synthesized the (1→6)-α-linked bigalactosides ( Figure S2c ), similar to all known melibiases of the GH 36 family [ 16 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ] and to their closely-related GH 27 representatives [ 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. Furthermore, α-PsGal formed the (1→4)-α-linked bigalactosides as described for mesophilic terrestrial α- d -galactosidases from Bifidobacterium breve 203 [ 35 ], Lactobacillus reuteri [ 16 ], and the acidic GH 27 family α- d -galactosidases (AgaBf3S) from the bacterium Bacteroides fragilis .…”
Section: Discussionmentioning
confidence: 89%